Experimental Study on the Compressive Strength of Big Mobility Concrete with Nondestructive Testing Method - Huai-Shuai Shang; Ting-Hua Yi; Lu-Sheng Yang (Advances in Materials Science and Engineering)
An experimental study of C20, C25, C30, C40, and C50 big mobility concrete cubes that came from laboratory and construction site was completed. Nondestructive testing (NDT) was carried out using impact rebound hammer (IRH) techniques to establish a correlation between the compressive strengths and the rebound number. The local curve for measuring strength of the regression method is set up and its superiority is proved. The rebound method presented is simple, quick, and reliable and covers wide ranges of concrete strengths. The rebound method can be easily applied to concrete specimens as well as existing concrete structures. The final results were compared with previous ones from the literature and also with actual results obtained from samples extracted from existing structures.